2020
DOI: 10.31018/jans.v12i4.2396
|View full text |Cite
|
Sign up to set email alerts
|

Modeling on population growth and its adaptation: A comparative analysis between Bangladesh and India

Abstract: The biggest challenge in the world is population growth and determining how society and the state adapt to it as it directly affects the fundamental human rights such as food, clothing, housing, education, medical care, etc. The population estimates of any country play an important role in making the right decision about socio-economic and population development projects. Unpredictable population growth can be a curse. The purpose of this research article is to compare the accuracy process and proximity of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The analysis showed a downward trend in the population. In [7], a study was carried out using the logistic model and least square model to do a comparative study for making predictions of population growth between Bangladesh and India at the end of the 21st century. It was found that the projection data from 2000 * This is an open access under a CC BY-NC-SA 4.0 license (https://creativecommons.org/licenses/by-nc-sa/4.0/) to 2020 using the established models closely match the real data.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis showed a downward trend in the population. In [7], a study was carried out using the logistic model and least square model to do a comparative study for making predictions of population growth between Bangladesh and India at the end of the 21st century. It was found that the projection data from 2000 * This is an open access under a CC BY-NC-SA 4.0 license (https://creativecommons.org/licenses/by-nc-sa/4.0/) to 2020 using the established models closely match the real data.…”
Section: Introductionmentioning
confidence: 99%